Integration of renewable energy into present and future energy systems - Sims, Ralph (2011)
To achieve higher renewable energy (RE) shares than the low levels typically found in present energy supply systems will require additional integration efforts starting now and continuing over the longer term. These include improved understanding of the RE resource characteristics and availability, investments in enabling infrastructure and research, development and demonstrations (RD&D), modifications to institutional and governance frameworks, innovative thinking, attention to social aspects, markets and planning, and capacity building in anticipation of RE growth.This chapter examines the means by which larger shares of RE could be integrated into the wide range of energy supply systems and also directly into end-user sectors at national and local levels. It outlines how RE resources can be used through integration into energy supply networks that deliver energy to consumers using energy carriers with varying shares of RE embedded or directly by the transport, buildings, industry and agriculture end-use sectors.